2003
DOI: 10.1623/hysj.48.3.413.45280
|View full text |Cite
|
Sign up to set email alerts
|

Effect of warmer climate on the depletion of snow-covered area in the Satluj basin in the western Himalayan region

Abstract: The effect of warmer climate on the depletion of snow-covered area has been evaluated for the Satluj River basin located in the western Himalayan region in India. Snowmelt runoff contributes substantially to the annual streamflow of this river. In order to study the impact of three warming scenarios (T+1, T+2 and T+3°C), more than 160 new snow depletion curves were prepared for different elevation zones of the basin over a study period of nine years (1985/86-1990/91 and 1996/97-1998/99). For each zone, the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Variations in the hydrological components will have a direct influence on the available water resources, demand and supply, water quality, soil moisture, groundwater reserves and frequency of floods and droughts in a basin. Hydrological and water resources studies are carried out at the basin scale (Mirza et al, 1998;Singh & Bengtsson, 2003. Therefore, information on climate change at the basin scale is of utmost importance for the planning, development and utilization of water.…”
Section: Scope Of the Present Studymentioning
confidence: 99%
“…Variations in the hydrological components will have a direct influence on the available water resources, demand and supply, water quality, soil moisture, groundwater reserves and frequency of floods and droughts in a basin. Hydrological and water resources studies are carried out at the basin scale (Mirza et al, 1998;Singh & Bengtsson, 2003. Therefore, information on climate change at the basin scale is of utmost importance for the planning, development and utilization of water.…”
Section: Scope Of the Present Studymentioning
confidence: 99%
“…Moreover, the rivers in the area are highly influenced by the snow (López-Moreno and García-Ruiz, 2004). Numerous studies have suggested that the impact of climate changes on hydrology will be especially pronounced in snow-fed basins (Singh and Bengtsson, 2003;Barnett et al, 2005), such as the headwaters located in the Pyrenees.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 shows the flow-diagram of the followed approach. SRM simulations are carried out in two ways: (i) with the annually constant value of LR taken as 0.65C/100 m, the most commonly used value of LR [6][7][8][9] and (ii) with the monthly varying values of near surface LR. For both runs, calibration has been done for 2001 and 2002 and the validation done for 2004 and 2005.…”
Section: Methodsmentioning
confidence: 99%
“…Two widely adopted snowmelt computation approaches are the temperature-index based and energy-budget based methods. However, due to the large extent and difficult accessibility of high mountainous terrain in Himalayas, most studies in the Himalayan basins have focussed on the temperature-index (T-index) based methods [6][7][8][9] . The T-index based approach, also known as the degreeday approach is a simple approach that assumes empirical relationship between air temperature and snow or ice melting rates 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation